Endometrial Preparation for Frozen–Thawed Embryo Transfer With or Without Pretreatment With GnRH Agonist: A Randomized Controlled Trial at Two Centers - Xu, Jian; Li, Shu-Zhen; Yin, Min-Na; Liang, Pei-Ling; Li, Ping; Sun, Ling (Frontiers in Endocrinology, 2021)
Objective: This prospective randomized controlled trial compared the reproductive outcomes of frozen embryo transfer (FET) with hormone replacement treatment (HRT) with or without GnRH agonist (GnRHa) pretreatment. Methods: A total of 133 patients scheduled for HRT‒FET mainly because of tubual and/or male factors who received 2 high-quality cleavage-stage embryos were enrolled at the two participating centers. The GnRHa group (n=65) received GnRHa pretreatment while the control group (n=68) did not. Analysis was based on the intention-to-treat (ITT) principle. Results: Among the 133 participants, 130 (97.7%) underwent ET and 127 (95.5%) completed the protocol. Clinical pregnancy rate according to ITT did not differ between the GnRHa and control groups (39/65 [60.0%) vs 41/68 [60.3%), P=0.887]; and implantation rate (47.6% vs 45.3%, P=0.713), early pregnancy loss rate (5.1% vs 19.5%, P=0.09), and live birth rate (49.2% vs 50.0%, P=0.920) were also comparable between groups. Conclusion: Pretreatment with GnRHa does not improve reproductive outcomes for women receiving HRT-FET.